Skeletal effects following developmental flame-retardant exposure are specific to sex and chemical class in the adult Wistar rat - Schkoda, Stacy; Horman, Brian; Witchey, Shannah K.; Jansson, Anton; Macari, Soraia; Patisaul, Heather B. (Frontiers in Toxicology, 2023)
A growing body of evidence is revealing that endocrine disrupting chemicals (EDCs) can disrupt aspects of metabolic programming suggesting skeletal development may be at risk; a possibility that is rarely examined. The commercial flame retardant (FR) mixture, Firemaster 550 (FM 550), has repeatedly been shown to negatively influence metabolic programming raising concern that skeletal integrity may consequently be impaired. We have previously shown that gestational and lactational exposure to 1000 µg FM 550 negatively affected sex-specific skeletal traits in male, but not female, rats assessed at six months of age. Whether this outcome is primarily driven by the brominated (BFR) or organophosphate ester (OPFR) portions of the mixture is unknown, or if the effects persist to an older age. To address this, for the present study dams were orally exposed throughout gestation and lactation to either 1000 µg BFR, 1000 µg OPFR, or 2000 µg FM 550. Offspring (n=8/sex/exposure) were weaned at PND 21 and assessed for femoral cortical and trabecular bone parameters at eight months of age via high resolution xray micro-computed tomography (micro-CT). Serum levels of serotonin, osteocalcin, alkaline phosphatase, and calcium were quantified. FM 550 affected both sexes but the females were more appreciably impacted by the OPFRs while the males were more vulnerable to the BFRs. While sex-specificity was expected due to the sexual dimorphic nature of skeletal physiology, the mechanisms accounting for the male and female specific phenotypes remain to be determined. Future work aims to clarify these unresolved issues.